PENGARUH PERBAIKAN KURSI KERJA TERHADAP KELUHAN MUSKULOSKELETAL PADA PEKERJAAN MENJAHIT DI DESA X - Eka Rosanti; Dasri Wulandari (Universitas Darussalam Gontor, 2016)
The objective of research is to find out and to study the effect of work seat reparation on the musculoskeletal complaints in sewing task in X Village. The research method employed in this study was a Quasi Experiment with one group pre-test and post-test design. The sampling technique used was random sampling. Random sampling means the selection of a group of subject through restriction obtained with inclusion and exclusion criteria. In this research, the population number was 31 male workers. The subject was done using random sampling with restriction so that 15 workers qualifying the inclusion and exclusion were obtained as the sample. The data collection was done using Anthropometry measurement, the work seat measurement before reparation, the administration of ergonomic seat according to the worker’s anthropometry and the use of Nordic body map questionnaire to find out the musculoskeletal complaints. Technique of processing and analyzing data used was nonparametric statistic test-wilcoxon test using SPSS version 16.0 computer software. The result of analysis on the difference of musculoskeletal complaints before and after the treatment using wilcoxon test shows the Asymp. Sig value (2-tailed) of 0.001 (P Value 0.001 < 0.01) means very significant that there is a value difference before and after the work seat reparation. After the work seat reparation the average (X) ± SD total score of musculoskeletal complaints decreases from 65.1 ± 3.1 to 41.3 ± 3.8. So the difference of musculoskeletal complaints is 23.8 (36.6%). The conclusion can be drawn that there is an effect of work seat reparation on the musculoskeletal complaints in sewing task in X Village. To prevent the musculoskeletal complaints, the ergonomic work seat in this research can be used. Keywords: Anthropometry; ergonomic seat; non-ergonomic seat; musculoskeletal complaints